THE IMPACT OF DIGITAL TECHNOLOGIES ON MULTICHANNEL RETAILING: FUTURE TRENDS AND RESEARCH DIRECTIONS - Divya Yadav; Jyoti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This paper examines the influence of emerging digital technologies on multichannel retailing, particularly regarding customer experience and retailer performance. A systematic literature review reveals that technologies like Artificial Intelligence (AI), the Internet of Things (IoT), Augmented and Virtual Reality (AR/VR), and Big Data enhance personalized shopping experiences and operational efficiency. However, challenges such as high costs, data privacy issues, and integration difficulties are noted. The study also identifies a research gap concerning the long-term effects of technology on customer loyalty and retailer profitability, while synthesizing current insights and proposing future research directions.